Designing surveys for radiography and radiation therapy. - O'Connor, Moira; Halkett, Georgia (Australian Institute of Radiography, 2010)
Surveys using standardised questionnaires are frequently used in the health area for research, to gather information to inform or improve clinical practice and to gage perceptions or attitudes towards particular issues. As we begin to conduct more studies in the areas of radiography and radiation therapy we need to ensure that it is essential that we use reliable and valid research methods so that findings are robust and, importantly, useable in clinical practice. This review focuses on how to design the questionnaire and highlights some key rules to help avoid the many pitfalls in survey design. The importance of the planning stage and time spent reviewing and revising questions is emphasised and the benefits and challenges of using existing instruments are discussed. Questionnaire layout is addressed and also the wording of individual questions as both of these will affect response rates and how people interpret questions. Wording can be difficult and may take a few drafts to get right. Several examples are given to demonstrate the concepts. The key messages in this review are: spend time planning and make the questionnaire brief, easy and safe. Issues such as response rates, types of questions, how to test for reliability and validity; and how to analyse the data will be covered in a further review for The Radiographer.